Peran Perguruan Tinggi Islam dalam Mencerdaskan Bangsa - Rauf, Fathurrahman (Buletin Al-Turas, 2007)
According to Human Development Report 2005, the quality index of Indonesian human resources showed the point 0.697 and reached the 110th levelfrom 177 observed countries. Compare with Vietnam. Indonesia is two level under it Vietnam reached 108th level with index 0.708. It means the role of country to develop people is still far from expectation. In this context, the role of all civil society pillars particularly university must be distinguished. Moreover, university faced big challenges after occuring economic, monetary and political crisis, and develop the social anomaly implied unsucces (failure) country.